Performance analysis of a planar solid oxide fuel cell stack between 750 degrees C and 500 degrees C - Lenser, Christian; Zurek, Joanna; Naumenko, Dmitry; Thieu, Cam-Anh; Son, Ji-Won; de Haart, Ute; Fang, Qingping; Blum, Ludger; Menzler, Norbert H. (ELSEVIER, 2020)
The performance of a planar SOFC stack using anode-supported cells (ASC) specifically developed for low temperature operation is discussed. The performance in single cell tests is compared to the stack performance, and important issues leading to a loss of performance in the stack are discussed. Based on the analysis of the contribution of the cell components to the decreasing performance below 600 degrees C, it is demonstrated that the thin electrolyte contributes only a small fraction of the ohmic resistance in stack operation, and that further improvement of the electrolyte may yield insignificant improvements in stack performance. The anode has the largest contribution to cell impedance in both cell and stack tests. The implications of a cell optimized for low-temperature operation on the stack sealing and anode reduction procedures are briefly discussed, exemplified by the performance loss of the cathode during stack sealing. In addition, an unusual breakaway-type oxidation is found on a thin Crofer 22 APU foil in the cathode air compartment, which is likely related to the low operation temperature of the stack. These findings highlight the most pressing issues of cell and stack development for low temperature applications, and provide a guide toward stack operation at 500 degrees C.
Keywords: FERRITIC STEELS; INTERCONNECT MATERIALS; OXIDATION BEHAVIOR; WATER-VAPOR; TEMPERATURE; ELECTRODE; LIFETIME; CONTACT; MODEL; LAYER